"A new animal": student activism and the Kenyan state in an era of multiparty politics, 1991–2000. Issue 4 (1st October 2020) - Melchiorre, Luke
ABSTRACT: This article explores the impact of the reintroduction of multiparty politics at the University of Nairobi in the late-1990s. It argues that the reinstatement of Nairobi's student union (SONU) in 1998 represented a fundamental turning point in the history of student activism in Kenya. SONU's return served to open space on campus for national political parties, particularly the ruling party, the Kenya African National Union (KANU), to play a greater role in student politics than they ever had before. The growing influence of these external actors and the support that they provided to candidates vying for SONU positions fundamentally altered the nature and practice of student politics at Nairobi in several important ways: exacerbating internal divisions within the student leadership along party and ethnic lines; contributing to the commercialization of student politics to an unprecedented degree; and driving a spike in intra-student violence through the creation of externally supported "goon squads." In documenting this history, this article challenges the conventional historical periodization of student politics at African universities in the 1990s and 2000s, which has tended to exclusively understand student activists as key actors in protesting against Structural Adjustment Policies and in promoting processes of democratization.